Efficacy and safety of intra-articular injection of tropomyosin receptor kinase A inhibitor in painful knee osteoarthritis: a randomized, double-blind and placebo-controlled study. Issue 11 (November 2019) - Krupka, E.; Jiang, G.-L.; Jan, C.
Summary: Objective: This trial evaluated the efficacy and safety of GZ389988A, a tropomyosin receptor kinase A (TrkA) inhibitor, in subjects with painful knee osteoarthritis (OA). Method: In this single center, double-blind, placebo-controlled and randomized trial, 104 subjects with moderate-to-severe knee OA pain were enrolled to receive a single intra-articular (IA) injection of either GZ389988A or placebo. Efficacy measures were assessed over 12 weeks and included walking pain (Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC] A1), overall knee pain, WOMAC A, B, C and total score, Patient Global Impression of Change (PGIC), OMERACT-OARSI responder rate and rescue medication use. Adverse events (AEs) were monitored up to 24 weeks. Results: The primary efficacy endpoint was met with a between-group difference of −7.49 (VAS 0–100) on WOMAC A1 changes over 4 weeks ( P  < 0.05 favoring GZ389988A). The secondary outcome on WOMAC A1 changes over 12 weeks had a between-group difference of −6.78 ( P  = 0.064). Among weekly assessments, statistically significant greater improvement in the GZ389988A group was observed in WOMAC A1, overall knee pain and/or WOMAC A at weeks 2–5. Although not statistically significant, improvements over placebo on pain and WOMAC C persisted over 12 weeks. Greater AE incidence was observed in the GZ389988A group including transient and self-limited injection joint inflammatory reactions with a spike of acetaminophen intake within the first week post-injection. Conclusion: IA injection of TrkA inhibitor GZ389988A in knee OA subjects reduced pain with a numerically functional gain and an acceptable safety profile. (ClinicalTrials.gov, NCT02845271 ).